(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current status of full and timely immunization with eight types of vaccines among children under 12 months of age at the Quynh Mai ward Health Station, Hai Ba Trung district, Hanoi city and analyze factors related to full and timely vaccination. Subjects and methods: Conducted on 100 children with expanded vaccination in Quynh Mai ward, Hai Ba Trung district, Hanoi city from January to March 2025. Cross-sectional descriptive research design and direct interview technique were used to collect information from child caregivers using a pre-prepared questionnaire combined with retrospective vaccination records. Results: The rate of full immunization with eight types of vaccines among children under 12 months of age was 96%, while the rate of timely immunization was 89%. Several factors were found to be associated with higher rates of full and timely immunization, including: caregivers aged ≤ 30 years; education level of at least intermediate vocational training; civil servants or public employees; children who were born full-term and had never been hospitalized. Conclusion: Full immunization with eight types of vaccines among children under 12 months of age was 96%, while the rate of timely immunization was 89%. An association between full and timely immunization rates and factors such as caregiver age, educational level, occupation, sources of immunization information, whether the child was born full-term and had never been hospitalized. These findings serve as a foundation for proposing appropriate interventions to improve expanded program on immunization coverage at local health stations in subsequent phases.